ANALISIS DAN PERANCANGAN SISTEM PENDAFTARAN PENGAJUAN DANA KERJA LAPANGAN DI YAYASAN CAPPA KEADILAN EKOLOGI BERBASIS WEBSITE - Fiqa Khairunnisa; Fitria Fatimah Zahara; Muhammad Andre; Gustinar Gustinar (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2024)
In this era of globalization where advances in information and communication technology (ICT) are growing rapidly and the use of IT in the field of organizations. As with the CAPPA Foundation's Ecological Justice Systems, information systems have. An important role in an institution or organization to help effectiveness and performance. This designed system is intended to process financial data, especially in the field of travel transportation money.The main purpose of creating a financial information system is to process financial data quickly and accurately, because the manual system that is still used causes several problems, such as not producing 100% accurate data and the travel transportation financial data processing system.Manual administration also takes a long time. Based on the problem analysis, the author tries to design a transportation financial information system that is expected to support financial data reporting so that the resulting report is faster and more accurate